Simultaneous measurement of tissue oxygen level‐dependent (TOLD) and blood oxygenation level‐dependent (BOLD) effects in abdominal tissue oxygenation level studies. Issue 5 (7th June 2013) - Ding, Yao; Mason, Ralph P.; McColl, Roderick W.; Yuan, Qing; Hallac, Rami R.; Sims, Robert D.; Weatherall, Paul T.
Abstract : Purpose: To assess oxygenation in abdominal organs with magnetic resonance imaging (MRI), a novel approach is presented to simultaneously measure both T1 ‐ and T 2 * ‐maps serially during a single dynamic MRI scan in response to an oxygen challenge. Materials and Methods: The proposed acquisition scheme consists of a multishot multiecho gradient echo planar imaging sequence (ms‐GEPI) interleaved with a multishot inversion recovery echo planar imaging (ms‐IR‐EPI) sequence. Respiratory motion compensation was accomplished with standard belt triggering and by acquiring all image data at the same phase of expiration. This respiratory‐triggered, free‐breathing, interleaved tissue oxygenation level‐dependent (TOLD) and blood oxygenation level‐dependent (BOLD) acquisition technique was validated on phantoms and seven healthy volunteers in response to an oxygen challenge. Results: Measurements of relaxation times both in vitro and in vivo were in good agreement with those obtained using conventional pulse sequences and reported in the literature. The interleaved sequence was able to measure oxygen‐induced relaxation time changes in human abdominal organs. Conclusion: The free‐breathing respiratory‐triggered interleaved T1 and T 2 * sequence successfully provided relaxation time maps of abdominal organs in a dynamic scan without the need for image registration. The simultaneous monitoring of tissue and blood oxygenation improves time efficiency and should enhance studies comparing dynamic T1 and T 2 * data within the abdomen. J. Magn. Reson. Imaging 2013;38:1230–1236. © 2013 Wiley Periodicals, Inc.